PENGARUH PENERAPAN E-FILING, PEMAHAMAN PERPAJAKAN, DAN SOSIALISASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DENGAN PEMAHAMAN INTERNET SEBAGAI VARIABEL MODERATING: Studi Kasus Wajib Pajak Yang Terdaftar di KPP Pratama Medan Belawan - Vena Miranda Gultom; Muhammad Arief; Ahmad Sani (METHOSIKA: Jurnal Akuntansi dan Keuangan Methodist, 2022)
The examination intends to decide the impact of the utilization of e-filing, understanding of taxation, and socialization of taxation on taxpayer compliance with the understanding of the internet as a moderating variable at KPP Pratama Medan Belawan. The type of research used in the research is associative research. The sample of this research is 100 individual taxpayers registered at KPP Pratama Medan Belawan. The data analysis technique used is mutiple linear regression analysis. The outcomes showed that the utilization of its showed that the application of e-filing and understanding of taxation had no significant effect on taxpayer compliance, taxation socialization and internet understanding had a significant effect on taxpayer compliance. Understanding the internet is not able to moderate the relationship between the effect of the implementation of e-filing on taxpayer compliance. understanding the internet is not able to moderate the relationship between the effect of understanding taxation on taxpayer compliance, and understanding the internet is not able to moderate the relationship between the effect of tax socialization on tax payer compliance.